2023
DOI: 10.3390/biomedicines11082271
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Hypertension: Mechanisms Involved and Modifying Factors for Effective Glucose Control

Abstract: Factors such as aging, an unhealthy lifestyle with decreased physical activity, snacking, a standard Western diet, and smoking contribute to raising blood pressure to a dangerous level, increasing the risk of coronary artery disease and heart failure. Atherosclerosis, or aging of the blood vessels, is a physiological process that has accelerated in the last decades by the overconsumption of carbohydrates as the primary sources of caloric intake, resulting in increased triglycerides and VLDL-cholesterol and ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 175 publications
0
5
0
1
Order By: Relevance
“…Furthermore, IR increases excessive glycosylation, which promotes the proliferation of vascular smooth muscle cells as well as cross-linking and deposition of collagen, all of which contribute to cardiac fibrosis and stiffening of the diastolic left ventricle 42 . Finally, IR-induced ectopic angiotensinogen production and incorrect renin–angiotensin–aldosterone system activation result in fluid retention and hypertension, which in turn cause cardiovascular events 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IR increases excessive glycosylation, which promotes the proliferation of vascular smooth muscle cells as well as cross-linking and deposition of collagen, all of which contribute to cardiac fibrosis and stiffening of the diastolic left ventricle 42 . Finally, IR-induced ectopic angiotensinogen production and incorrect renin–angiotensin–aldosterone system activation result in fluid retention and hypertension, which in turn cause cardiovascular events 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that insulin resistance can promote the formation of advanced glycation end products, increase oxidative stress and systemic inflammation, lead to mitochondrial dysfunction, dyslipidemia, endothelial dysfunction, decrease nitro oxide synthesis, and increase volume load. These mechanisms together lead to increased peripheral vascular resistance and preload, ultimately resulting in the development of hypertension [ 26 ]. Insulin resistance also plays a key role in the progression of hypertension-induced target organ damage, like left ventricular hypertrophy, atherosclerosis and chronic kidney disease [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, caffeine might impair insulin sensitivity and glucose metabolism [ 29 ]. Insulin resistance and dysregulated glucose metabolism are risk factors for hypertension and cardiovascular disease [ 30 ]. Sixth, caffeine interferes with intracellular calcium signaling, which plays a crucial role in smooth muscle contraction and vascular tone regulation.…”
Section: Discussionmentioning
confidence: 99%